Contested Human Relations of Commodity Culture in The Tempest, Robinson Crusoe and Jane Eyre - Khanal, Niran (Political Science Journal, 2025)
This paper examines the impact of commodity culture in human relations in the contexts of The Tempest, Robinson Crusoe and Jane Eyre. The class differences as represented in the narratives cause the conflictual relations between the characters. The ownership of resources and exercise of power as the underlying motivations cause the divisions of society between the privileged and the underprivileged. In this context, I argue that commodity culture, the product of capitalism, shapes human relations in the selected narratives. The ideology of capitalism causes class differences as it promotes consumerism and converts human values and activities into commodities. The social identity, status and power relations of the characters are not free from the market driven cultures that value human activities as buying and selling products. Moreover, the class-based problems intersect with other social marginalization, like racism and gender practices. So, the study tries to address class contradictions along with the embedded issues of race and gender. To meet this goal, for theoretical applications, I draw insights from Marxism, feminism and Deconstruction. For the purpose of examining the differences in representations of commodity culture and class related issues, I explore the alternative texts, A Tempest, Foe and Wide Sargasso Sea, of the above-mentioned texts. Therefore, the critical comparative approach is the method of study. This study is significant to foresee the alternative human relations that transcend the class binaries and critique the commodity culture. The key findings of this study are that in the selected mainstream narratives, human values, relations and labour are commodified as they are understood in the language of commerce. However, in the alternative narratives, such values and relations come under criticism for the better situations.